Understanding the effects of targeted modifications on the 1: 2 Choline And GEranate structure - Dobre,A; Koutsoukos,S; Philippi,F; Rauber,D; Kay,CWM; Palumbo,O; Roessler,MM; Welton,T (Physical Chemistry Chemical Physics, 2024)
1:2 Choline-and-geranate (CAGE) is an ionic liquid (IL) widely studied for its biomedical applications. However, both its industrial-scale preparation and its long-term storage are problematic so finding more suitable candidates which retain its advantageous properties is crucial. As a first step towards this we have conducted a targeted modification study to understand the effects of specific functional groups on the properties of CAGE. 1:2 Choline-and-octanoate and 1:2 butyltrimethylammonium-and-octanoate were synthesised and their thermal and rheological properties examined in comparison to those of CAGE. Using differential scanning calorimetry and polarising microscopy, the model compound was found to be an isotropic liquid, while the analogues were room-temperature liquid-crystals which transition to isotropic liquids upon heating. Dynamic mechanical analysis showed that the thermal behaviour of the studied systems was even more complex, with the ILs also undergoing a thermally-activated relaxation process. Furthermore, we have used electron paramagnetic resonance (EPR) spectroscopy, along with a variety of spin probes with different functional groups, in order to understand the chemical environment experienced by solutes in each system. The EPR spectra indicate that the radicals experience two distinct environments (polar and nonpolar) in the liquid-crystalline phase, but only one average environment in the isotropic phase. The liquid-crystalline phase experiments also showed that the relative populations of the two domains depend on the nature of the solutes, with polar or strongly hydrogen-bonding solutes preferring the polar domain. For charged solutes, the EPR spectra showed line-broadening, suggesting that their ionic nature leads to complex, unresolved interactions.